Local Wisdom of Southeast Sulawesi in Nurturing the Profile of Pancasila Students - Alfidayati, Alfidayati; Melisa, Windi (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
The implementation of character education through the Pancasila Student Profile faces challenges in its implementation due to limited adaptation to local contexts. This research aims to identify and analyze Southeast Sulawesi local wisdom values relevant to character formation according to the Pancasila Student Profile, and to formulate a model for integrating this local wisdom into the educational curriculum. The research uses a qualitative approach with educational ethnography methods, involving participatory observation, in-depth interviews with 24 key informants (traditional leaders, educators, and policy makers), and documentation studies of local cultural practices in four districts in Southeast Sulawesi. The results show that there are five local wisdom values that strongly correlate with the dimensions of the Pancasila Student Profile: (1) Kohanu (shame and dignity) supports the dimension of faith and piety; (2) Samaturu (mutual cooperation) strengthens the dimension of collaboration; (3) Merou (social care) sustains the dimension of global diversity; (4) Pombala (deliberation and critical thinking) develops the dimension of critical reasoning; and (5) Poashi-ashi (persistence and perseverance) builds the dimension of independence. The resulting integration model includes the development of local content based on cultural wisdom, the involvement of traditional leaders in learning, and cultural practices as extracurricular activities that strengthen the character of Pancasila Students based on the local values of Southeast Sulawesi communities.